A functional current collector for dry anode and its preparation method, dry anode and lithium-ion battery

CN122992084APending Publication Date: 2026-10-27YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611241983.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该功能集流体的整体结构设计能够同步解决传统铜箔重量大、回收污染严重、干法电极附着力差、锂沉积不均、界面易脱层以及高负载下稳定性不足等问题,从而显著提升电池的能量密度、循环稳定性与使用寿命

Benefits of technology

本申请通过非铜金属层替代传统铜层,从根源上避免了铜污染,同时有效提升了电池的质量能量密度;具有凹凸微锚定结构的界面微锚定过渡层可与干法电极层形成可靠的机械嵌合,显著增强干法负极与功能集流体之间的界面结合力。该功能集流体的整体结构设计能够同步解决传统铜箔重量大、回收污染严重、干法电极附着力差、锂沉积不均、界面易脱层以及高负载下稳定性不足等问题,从而显著提升电池的能量密度、循环稳定性与使用寿命。此外,该功能集流体与干法电极层配合构建的干法负极可实现无溶剂绿色制造,界面结合力可控,且在使用后能够实现干法电极层与功能集流体的完全分离,极大提升了回收效率。本申请在高能量密度、高可回收、绿色制造的锂离子电池领域具有显著的实用价值与广阔的规模化应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This application provides a functional current collector for dry-process anodes, its preparation method, a dry-process anode, and a lithium-ion battery. The functional current collector for dry-process anodes includes a polymer base film, and a non-copper metal layer and an interface micro-anchoring transition layer sequentially disposed on at least one surface of the polymer base film. The interface micro-anchoring transition layer has a concave-convex micro-anchoring structure. This application avoids copper contamination by replacing the traditional copper layer with a non-copper metal layer, while effectively improving the battery's mass energy density. The interface micro-anchoring transition layer with its concave-convex micro-anchoring structure can form a reliable mechanical interlock with the dry-process electrode layer, significantly enhancing the interfacial bonding force between the dry-process anode and the functional current collector. The overall structural design of this functional current collector can simultaneously solve problems such as the large weight of traditional copper foil, severe recycling pollution, poor adhesion of dry-process electrodes, uneven lithium deposition, easy interface delamination, and insufficient stability under high loads, thereby significantly improving the battery's energy density, cycle stability, and lifespan.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery materials technology, specifically relating to a functional current collector for dry negative electrode and its preparation method, dry negative electrode and lithium-ion battery. Background Technology

[0002] Lithium-ion batteries have been widely used in new energy vehicles and large-scale energy storage, placing higher demands on their energy density, safety, and green manufacturing. The negative electrode current collector and electrode fabrication process are key factors determining the overall performance of the battery. Currently, commercial systems commonly use copper foil as the negative electrode current collector, combined with a wet NMP coating process to fabricate the electrode. However, copper foil accounts for a high proportion of battery mass, is scarce, and its recycling process causes significant pollution; the wet process relies on toxic solvents, consumes a lot of energy, and is prone to cracking and failure when fabricating thick electrodes. These problems have become major bottlenecks restricting the industry's development.

[0003] While traditional dry-process solvent-free electrodes eliminate NMP contamination and offer advantages such as high efficiency, low energy consumption, and good stability with thick electrodes, the interfacial bonding problem remains a persistent challenge. Commercial dry-process electrodes often use polytetrafluoroethylene (PTFE) as a single binder. Due to PTFE's non-polar properties, the adhesion between the electrode and the metal current collector is extremely poor. Under high load, high rate, or long-cycle conditions, interfacial delamination and material shedding are highly likely to occur, leading to a sharp increase in internal resistance, reduced cycle life, and even short-circuit failures. Simply using traditional methods such as carbon coating and roughening has limited effectiveness and cannot meet the practical requirements of high-reliability batteries.

[0004] At the same time, copper-free, lightweight, and highly recyclable current collectors have become important development directions for the next generation of batteries. However, current research on copper-free current collectors is all done in conjunction with wet electrodes, which cannot simultaneously solve systemic problems such as copper pollution, heavy weight, poor adhesion of dry electrodes, and environmentally unfriendly processes. This greatly limits the technological breakthroughs of high-energy-density and highly sustainable lithium-ion batteries.

[0005] Therefore, how to simultaneously solve the problems of traditional copper foil's large weight, recycling pollution, poor adhesion of dry electrodes, uneven lithium deposition, easy delamination at the interface, and insufficient stability under high load, and significantly improve the energy density, cycle stability and service life of batteries, is an important direction of current research. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this application aims to provide a functional current collector for dry-process anodes, its preparation method, a dry-process anode, and a lithium-ion battery. This application replaces the traditional copper layer with a non-copper metal layer, fundamentally avoiding copper contamination while effectively improving the battery's mass energy density. An interface micro-anchoring transition layer with a concave-convex micro-anchoring structure can form a reliable mechanical interlock with the dry-process electrode layer, significantly enhancing the interfacial bonding between the dry-process anode and the functional current collector. The overall structural design of this functional current collector simultaneously solves problems such as the heavy weight of traditional copper foil, severe recycling pollution, poor adhesion of dry-process electrodes, uneven lithium deposition, easy interface delamination, and insufficient stability under high loads, thereby significantly improving the battery's energy density, cycle stability, and lifespan. Furthermore, the dry-process anode constructed using this functional current collector and the dry-process electrode layer can achieve solvent-free green manufacturing, with controllable interfacial bonding, and can achieve complete separation of the dry-process electrode layer and the functional current collector after use, greatly improving recycling efficiency. This application has significant practical value and broad prospects for large-scale application in the field of high-energy-density, highly recyclable, and green-manufacturing lithium-ion batteries.

[0007] To achieve the purpose of this application, the following technical solution is adopted: In a first aspect, this application provides a functional current collector for dry negative electrodes, the functional current collector comprising: Polymer-based film.

[0008] A non-copper metal layer is disposed on at least one side surface of the polymer base film.

[0009] An interface micro-anchoring transition layer, having a concave-convex micro-anchoring structure, is disposed on the surface of the non-copper metal layer away from the polymer base film.

[0010] This application replaces the traditional copper layer with a non-copper metal layer, fundamentally avoiding copper contamination while effectively improving the battery's mass energy density. The interface micro-anchoring transition layer with its uneven micro-anchoring structure can form a reliable mechanical interlock with the dry electrode layer, significantly enhancing the interfacial bonding between the dry electrode and the functional current collector, ensuring the stability of the dry electrode layer. The overall structural design of this functional current collector simultaneously solves problems such as the heavy weight of traditional copper foil, severe recycling pollution, poor adhesion of dry electrodes, uneven lithium deposition, easy interface delamination, and insufficient stability under high loads, thereby significantly improving the battery's energy density, cycle stability, and lifespan. Furthermore, the dry electrode constructed using this functional current collector and the dry electrode layer can achieve solvent-free green manufacturing, with controllable interfacial bonding, and can achieve complete separation of the dry electrode layer and the functional current collector after use, greatly improving recycling efficiency. This application has significant practical value and broad prospects for large-scale application in the field of high-energy-density, highly recyclable, and green-manufacturing lithium-ion batteries.

[0011] In some embodiments, the thickness of the polymer base film is 10-20 μm, for example, it can be 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or 20 μm.

[0012] This application does not limit the type of polymer-based film. For example, it may be polyethylene terephthalate film (PET film).

[0013] In some embodiments, the thickness of the non-copper metal layer is 0.3-1 μm, for example, it can be 0.3 μm, 0.5 μm, 0.7 μm, 0.9 μm or 1.0 μm.

[0014] In this application, the appropriate thickness of the non-copper metal layer can reduce weight and increase the energy density of the battery, while ensuring good conductivity and interfacial bonding strength. If the thickness is too thin, it will easily lead to excessive sheet resistance, insufficient conductivity, and increased cycle voltage drop of the battery; if the thickness is too thick, it will weaken the weight reduction advantage, increase the internal stress of the layer, make it prone to cracking when bent, and increase the cost.

[0015] In some embodiments, the surface roughness Ra of the non-copper metal layer is 20-80 nm, for example, it can be 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm or 80 nm.

[0016] In this application, the surface roughness Ra of the non-copper metal layer is within a suitable range, which can homogenize the lithium-ion flux, reduce the nucleation overpotential, guide uniform lithium deposition, and suppress dendrite growth, thus satisfying the dual functions of homogenizing lithium-ion flux and mechanical anchoring. If the surface roughness Ra is too small, the smoothness will be too high, resulting in weak mechanical interlocking with the transition layer and easy delamination; if the surface roughness Ra is too large, local peaks will easily induce lithium dendrites, uneven current distribution, and accelerated battery cycle degradation.

[0017] In some embodiments, the thickness ratio of the non-copper metal layer to the interface micro-anchoring transition layer is (3-5):1, for example, it can be 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, etc.

[0018] In this application, an appropriate thickness ratio can maintain a low interfacial resistance and a high peel strength while ensuring good interfacial anchoring effect, achieving a synergy between lightweight and high reliability. If the thickness ratio is too small, the interfacial micro-anchoring transition layer is too thick, the interfacial resistance increases, and the overall weight increases; if the thickness ratio is too large, the interfacial micro-anchoring transition layer is too thin, the anchoring structure is insufficient, and the peel strength decreases.

[0019] In some embodiments, the thickness of the non-copper metal layer is 0.3-0.8 μm, for example, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm or 0.8 μm.

[0020] In some embodiments, the surface roughness Ra of the non-copper metal layer is 30-50 nm, for example, it can be 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.

[0021] In some embodiments, the thickness ratio of the non-copper metal layer to the interface micro-anchoring transition layer is (3.5-4.5):1, for example, it can be 3.5:1, 3.8:1, 4:1, 4.2:1 or 4.5:1, etc.

[0022] In some embodiments, the material of the non-copper metal layer includes any one or a combination of at least two of elemental cobalt, elemental nickel, nickel-cobalt alloy, nickel-titanium alloy, elemental titanium, or elemental chromium.

[0023] In this application, elemental cobalt, nickel-cobalt alloys, and nickel-titanium alloys exhibit lithiophilicity, resistance to electrolyte corrosion, and a tendency to form uneven micro-anchoring structures on their surfaces, resulting in weight reduction and cycle performance close to that of elemental nickel. Elemental titanium and elemental chromium, on the other hand, possess extremely strong corrosion resistance, making them suitable for high-voltage, long-cycle applications, but their conductivity is slightly lower than that of elemental nickel.

[0024] In some embodiments, the interface micro-anchoring transition layer comprises a conductive carbon layer and / or a non-copper metal oxide layer. The non-copper metal oxide layer may, for example, be a nickel oxide layer.

[0025] In some embodiments, the sheet resistance of the non-copper metal layer is ≤0.1Ω / sq, for example, it can be 0.01Ω / sq, 0.03Ω / sq, 0.05Ω / sq, 0.08Ω / sq, or 0.1Ω / sq. It should be noted that the sheet resistance can be directly measured at room temperature using a four-probe sheet resistance tester.

[0026] In some embodiments, the interfacial peel strength of the non-copper metal layer is ≥1.2 N / cm, for example, it can be 1.2 N / cm, 1.5 N / cm, 1.8 N / cm, 2.0 N / cm, or 2.5 N / cm. It should be noted that the interfacial peel strength can be obtained by performing a 180° peel test using a universal tensile testing machine.

[0027] In some embodiments, the feature size of the concave-convex micro-anchoring structure in the direction perpendicular to the surface of the non-copper metal layer is 10-500 nm, for example, it can be 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, or 500 nm. It should be noted that the feature size can be obtained by scanning electron microscopy (SEM).

[0028] In this application, the concave-convex micro-anchoring structure with a certain height characteristic size can form a mechanical interlocking anchor with the subsequently deposited dry electrode layer, while retaining the conductive path, thus taking into account both adhesion and conductivity.

[0029] In some embodiments, the concave-convex micro-anchoring structure includes an island-like structure and a particle-stacked structure.

[0030] In some embodiments, the surface of the interface micro-anchoring transition layer is modified with active functional groups, including hydroxyl and / or carboxyl groups.

[0031] In this application, the surface of the interfacial micro-anchoring transition layer is modified with active functional groups, which can interact with the silane coupling agent in the subsequently deposited dry electrode layer to form stable covalent chemical bonds, thereby improving the interfacial bonding force at the chemisorption level.

[0032] Secondly, this application provides a method for preparing a functional current collector for a dry negative electrode as described in the first aspect, the method comprising the following steps: Provide polymer-based films.

[0033] A non-copper metal layer and an interface micro-anchoring transition layer are sequentially prepared on at least one side surface of the polymer base film to obtain the functional current collector for the dry negative electrode.

[0034] In some embodiments, the method for preparing the non-copper metal layer includes electron beam evaporation or magnetron sputtering.

[0035] In some embodiments, the process parameters in the electron beam evaporation method include: a vacuum degree of 2.5 × 10⁻⁶. -4 Pa-3×10 -4 Pa, for example, could be 2.5 × 10⁻⁶. -4 Pa, 2.6 × 10 -4 Pa, 2.7 × 10 -4 Pa, 2.8 × 10 -4 Pa, 2.9 × 10 -4 Pa or 3×10 -4 Pa, etc., have a deposition rate of 1-4 Å / s, for example, it can be 1 Å / s, 2 Å / s, 3 Å / s or 4 Å / s, etc.

[0036] In some embodiments, the method for preparing the interface micro-anchoring transition layer includes chemical vapor deposition or physical vapor deposition.

[0037] In some embodiments, the prepared interfacial micro-anchoring transition layer is further subjected to post-processing, the steps of which include: The interface micro-anchoring transition layer is etched to introduce active functional groups, including hydroxyl and / or carboxyl groups, onto its surface. Exemplarily, the etching process can be plasma etching or chemical etching.

[0038] Thirdly, this application provides a dry negative electrode, which includes a functional current collector as described in the first aspect, and a dry electrode layer disposed on the surface of the functional current collector.

[0039] The dry electrode layer includes a negative electrode active material and a composite binder, wherein the composite binder includes polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).

[0040] This application sets a dry electrode layer with the above composition on the surface of the interface micro-anchoring transition layer. The dual binder system synergistically enhances the electrode cohesion and interface adhesion (PTFE provides cohesion, and PVDF enhances interface adhesion). Together with the non-metallic layer and the interface micro-anchoring transition layer, a mechanical interlock is formed, which can solve the problems of easy detachment and high impedance of dry electrodes. Furthermore, this dry negative electrode can achieve solvent-free green manufacturing and can achieve complete separation of the dry electrode layer and the functional current collector after use, which greatly improves the recycling efficiency.

[0041] In some embodiments, the negative electrode active material includes graphite.

[0042] In some embodiments, the mass content of the negative electrode active material in the dry electrode layer is 95-96 wt%, for example, it can be 95 wt%, 95.5 wt%, or 96 wt%.

[0043] In some embodiments, the dry electrode layer further includes a conductive agent, such as conductive carbon black.

[0044] In some embodiments, the composite binder in the dry electrode layer has a mass content of 2-3 wt%, for example, it can be 2.0 wt%, 2.2 wt%, 2.5 wt%, 2.8 wt%, or 3.0 wt%.

[0045] In some embodiments, the mass ratio of polytetrafluoroethylene to polyvinylidene fluoride is (0.8-1.2):1, for example, it can be 0.8:1, 0.9:1, 1.0:1, 1.1:1 or 1.2:1, etc.

[0046] In some embodiments, the thickness of the dry electrode layer is 5-10 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0047] In some embodiments, the dry electrode layer further includes a silane coupling agent, wherein the silane coupling agent comprises 0.1-0.5 wt% by mass in the dry electrode layer, for example, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, or 0.5 wt%. Exemplarily, the silane coupling agent may be an amino-based silane coupling agent (such as KH-550) or an epoxy-based silane coupling agent (such as KH-560).

[0048] This application does not limit the preparation method of the dry negative electrode. For example, the following method can be used: mixing the negative electrode active material, composite binder and conductive agent for 30-60 min (e.g. 30 min, 40 min, 50 min or 60 min, etc.) to obtain dry electrode composite powder; spreading the dry electrode composite powder on the surface of the interfacial micro-anchoring transition layer of the functional current collector, and hot-pressing composite for 30-60 s (e.g. 160 ℃, 170 ℃ or 180 ℃, etc.) under the conditions of 160-180 ℃ and 8-12 MPa (e.g. 8 MPa, 9 MPa, 10 MPa, 11 MPa or 12 MPa, etc.) to obtain the dry negative electrode.

[0049] Fourthly, this application provides a lithium-ion battery, the lithium-ion battery comprising a dry negative electrode as described in the third aspect.

[0050] The numerical range described in this application includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values ​​included in the range.

[0051] Compared with the prior art, this application has the following advantages: This application replaces the traditional copper layer with a non-copper metal layer, fundamentally avoiding copper pollution while effectively improving the battery's mass energy density. The interface micro-anchoring transition layer with a concave-convex micro-anchoring structure can form a reliable mechanical interlock with the dry electrode layer, significantly enhancing the interfacial bonding between the dry anode and the functional current collector. The overall structural design of this functional current collector simultaneously solves problems such as the heavy weight of traditional copper foil, severe recycling pollution, poor adhesion of dry electrodes, uneven lithium deposition, easy interface delamination, and insufficient stability under high loads, thereby significantly improving the battery's energy density, cycle stability, and lifespan. Furthermore, the dry anode constructed using this functional current collector and the dry electrode layer can achieve solvent-free green manufacturing, with controllable interfacial bonding, and can achieve complete separation of the dry electrode layer and the functional current collector after use, greatly improving recycling efficiency. This application has significant practical value and broad prospects for large-scale application in the field of high-energy-density, highly recyclable, and green-manufacturing lithium-ion batteries. Detailed Implementation

[0052] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.

[0053] The scope of this application can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form a valid range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this application. In addition, if the minimum range values ​​1 and 2 are listed, and the maximum range values ​​3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this application. In this application, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0054] In this application, "at least two combinations" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or at least two combinations" means any one of the listed items, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this application. In this application, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this application, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.

[0055] In this application, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond those listed unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this application, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this application. The term "embodiment" as used in this application means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art can explicitly and implicitly understand that the embodiments described in this application can be combined with other embodiments that do not conflict with existing technologies. The ordinal numbers "first," "second," "third," and "fourth," etc., used in this application in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect," are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.

[0056] In this application, the order in which the steps are written in the methods described in the various embodiments does not imply a strict execution order. The actual execution order of each step should be determined according to its function and possible internal logic. Unless otherwise specified, all steps in this application can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.

[0057] Example 1 This embodiment provides a functional current collector for dry negative electrodes, the functional current collector comprising: PET film.

[0058] A nickel layer is disposed on one side surface of the PET film.

[0059] An interface micro-anchoring transition layer, having a concave-convex micro-anchoring structure, is disposed on the side of the nickel layer away from the PET film.

[0060] The PET film has a thickness of 15 μm; the nickel layer has a thickness of 0.5 μm, a surface roughness Ra of 50 nm, a sheet resistance ≤0.1 Ω / sq, and a thickness ratio of 4:1 between the nickel layer and the interface micro-anchoring transition layer; the interface micro-anchoring transition layer is a nickel oxide layer; the feature size of the uneven micro-anchoring structure in the direction perpendicular to the surface of the nickel layer is 10-500 nm; the uneven micro-anchoring structure includes island-like structures and particle-stacked structures.

[0061] This embodiment also provides a method for preparing the above-mentioned functional current collector for dry negative electrodes, the preparation method comprising the following steps: We provide PET film.

[0062] A nickel layer with a thickness of 0.5 μm was deposited on one side surface of the PET film using electron beam evaporation. The process parameters for electron beam evaporation included: a vacuum degree of 3 × 10⁻⁶. -4 Pa, deposition rate is 2.5 Å / s.

[0063] A nickel oxide layer with a thickness of 0.125 μm was deposited on the surface of the nickel layer using chemical vapor deposition to obtain the functional current collector for the dry negative electrode.

[0064] This embodiment also provides a dry negative electrode, which includes the functional current collector as described above, and a dry electrode layer disposed on the surface of the functional current collector.

[0065] The dry electrode layer comprises a negative electrode active material, a composite binder, and a conductive agent. The composite binder comprises PTFE and PVDF in a mass ratio of 1:1. The negative electrode active material is graphite. The mass content of the negative electrode active material in the dry electrode layer is 96 wt%. The mass content of the composite binder in the dry electrode layer is 2 wt%. The thickness of the dry electrode layer is 7 μm. The conductive agent is conductive carbon black.

[0066] This embodiment also provides a method for preparing the above-mentioned dry negative electrode, including the following steps: The negative electrode active material, composite binder and conductive agent are mixed for 45 min to obtain dry electrode composite powder; the dry electrode composite powder is spread on the surface of the interface micro-anchoring transition layer of the functional current collector, and hot-pressed composite at 170℃ and 10MPa for 45 s, and then densified by room temperature roll pressing to obtain the dry negative electrode.

[0067] This embodiment also provides a CR2032 coin cell, which includes a positive electrode, a dry negative electrode as described above, a separator, an electrolyte, and a coin cell casing.

[0068] The positive electrode is a nickel-cobalt-manganese ternary positive electrode, wherein the loading of the nickel-cobalt-manganese positive electrode active material (NCM811) is 5 mg / cm³. 2 N / P = 1.1; The diaphragm includes a polyethylene base membrane and a ceramic coating disposed on both sides of the base membrane; The electrolyte includes lithium hexafluorophosphate with a concentration of 1 mol / L, and the solvent is a composite solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:1).

[0069] Example 2 This embodiment provides a functional current collector for dry negative electrodes, the functional current collector comprising: PET film.

[0070] A nickel layer is disposed on one side surface of the PET film.

[0071] An interface micro-anchoring transition layer, having a concave-convex micro-anchoring structure, is disposed on the side of the nickel layer away from the PET film.

[0072] The PET film has a thickness of 20 μm; the nickel layer has a thickness of 0.8 μm, a surface roughness Ra of 20 nm, a sheet resistance ≤0.1 Ω / sq, and a thickness ratio of 4:1 between the nickel layer and the interface micro-anchoring transition layer; the interface micro-anchoring transition layer is a nickel oxide layer; the feature size of the uneven micro-anchoring structure in the direction perpendicular to the surface of the nickel layer is 10-500 nm; the uneven micro-anchoring structure includes island-like structures and particle-stacked structures.

[0073] This embodiment also provides a method for preparing the above-mentioned functional current collector for dry negative electrodes, the preparation method comprising the following steps: We provide PET film.

[0074] A nickel layer with a thickness of 0.8 μm was deposited on one side surface of the PET film using electron beam evaporation. The process parameters for electron beam evaporation included: a vacuum degree of 3 × 10⁻⁶. -4 Pa, deposition rate is 1 Å / s.

[0075] A nickel oxide layer with a thickness of 0.2 μm was deposited on the surface of the nickel layer using chemical vapor deposition to obtain the functional current collector for the dry negative electrode.

[0076] This embodiment also provides a dry negative electrode, which includes the functional current collector as described above, and a dry electrode layer disposed on the surface of the functional current collector.

[0077] The dry electrode layer comprises a negative electrode active material, a composite binder, and a conductive agent. The composite binder comprises PTFE and PVDF in a mass ratio of 1:1. The negative electrode active material is graphite. The mass content of the negative electrode active material in the dry electrode layer is 96 wt%. The mass content of the composite binder in the dry electrode layer is 2 wt%. The thickness of the dry electrode layer is 10 μm. The conductive agent is conductive carbon black.

[0078] This embodiment also provides a method for preparing the above-mentioned dry negative electrode, including the following steps: The negative electrode active material, composite binder and conductive agent are mixed for 30 min to obtain dry electrode composite powder; the dry electrode composite powder is spread on the surface of the interface micro-anchoring transition layer of the functional current collector, and hot-pressed composite at 180℃ and 12MPa for 60 s, and then densified by room temperature roll pressing to obtain the dry negative electrode.

[0079] This embodiment also provides a 0.5Ah soft-pack battery, which includes a positive electrode, a dry negative electrode as described above, a separator, an electrolyte, and an aluminum-plastic film casing.

[0080] The positive electrode is a nickel-cobalt-manganese ternary positive electrode, wherein the loading of the nickel-cobalt-manganese positive electrode active material (NCM811) is 8 mg / cm³. 2 N / P=1.2; the diaphragm includes a polyethylene base membrane and a ceramic coating disposed on both sides of the base membrane; the electrolyte includes lithium hexafluorophosphate with a concentration of 1 mol / L, and the solvent is a composite solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:1).

[0081] Example 3 This embodiment provides a functional current collector for dry negative electrodes, the functional current collector comprising: PET film.

[0082] A nickel layer is disposed on one side surface of the PET film.

[0083] An interface micro-anchoring transition layer, having a concave-convex micro-anchoring structure, is disposed on the side of the nickel layer away from the PET film.

[0084] The PET film has a thickness of 10 μm; the nickel layer has a thickness of 0.3 μm, a surface roughness Ra of 80 nm, a sheet resistance ≤0.1 Ω / sq, and a thickness ratio of 3:1 between the nickel layer and the interface micro-anchoring transition layer; the interface micro-anchoring transition layer is a nickel oxide layer; the feature size of the uneven micro-anchoring structure in the direction perpendicular to the surface of the nickel layer is 10-500 nm; the uneven micro-anchoring structure includes island-like structures and particle-stacked structures.

[0085] This embodiment also provides a method for preparing the above-mentioned functional current collector for dry negative electrodes, the preparation method comprising the following steps: We provide PET film.

[0086] A nickel layer with a thickness of 0.3 μm was deposited on one side surface of the PET film using electron beam evaporation. The process parameters for electron beam evaporation included: a vacuum degree of 3 × 10⁻⁶. -4 Pa, deposition rate is 4 Å / s.

[0087] A nickel oxide layer with a thickness of 0.1 μm was deposited on the surface of the nickel layer using chemical vapor deposition to obtain the functional current collector for the dry negative electrode.

[0088] This embodiment also provides a dry negative electrode, which includes the functional current collector as described above, and a dry electrode layer disposed on the surface of the functional current collector.

[0089] The dry electrode layer comprises a negative electrode active material, a composite binder, and a conductive agent. The composite binder comprises PTFE and PVDF in a mass ratio of 1.2:1. The negative electrode active material is graphite. The dry electrode layer contains 95.5 wt% of the negative electrode active material. The dry electrode layer contains 2.5 wt% of the composite binder. The dry electrode layer has a thickness of 5 μm. The conductive agent is conductive carbon black.

[0090] This embodiment also provides a method for preparing the above-mentioned dry negative electrode, including the following steps: The negative electrode active material, composite binder and conductive agent are mixed for 45 min to obtain dry electrode composite powder; the dry electrode composite powder is spread on the surface of the interface micro-anchoring transition layer of the functional current collector, and hot-pressed composite at 160℃ and 8MPa for 30 s, and then densified by room temperature roll pressing to obtain the dry negative electrode.

[0091] This embodiment also provides a CR2032 coin cell, which includes a positive electrode, a dry negative electrode as described above, a separator, an electrolyte, and a coin cell casing.

[0092] The positive electrode is a nickel-cobalt-manganese ternary positive electrode, wherein the loading of the nickel-cobalt-manganese positive electrode active material (NCM811) is 4 mg / cm³. 2 N / P=1; The diaphragm includes a polyethylene base membrane and a ceramic coating disposed on both sides of the base membrane; The electrolyte includes lithium hexafluorophosphate with a concentration of 1 mol / L, and the solvent is a composite solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:1).

[0093] Example 4 The difference between this embodiment and Embodiment 1 is that the nickel layer is replaced by a cobalt layer; the cobalt layer has a thickness of 0.3 μm and a surface roughness Ra of 30 nm; the thickness ratio of the cobalt layer to the interface micro-anchoring transition layer is 3.5:1; and the interface micro-anchoring transition layer is a conductive carbon layer.

[0094] The remaining preparation methods and parameters are consistent with those in Example 1.

[0095] Example 5 The difference between this embodiment and Embodiment 1 is that the nickel layer is replaced by a nickel-cobalt alloy layer; the thickness of the nickel-cobalt alloy layer is 0.8 μm and the surface roughness Ra is 40 nm; the thickness ratio of the nickel-cobalt alloy layer to the interface micro-anchoring transition layer is 4.5:1.

[0096] The remaining preparation methods and parameters are consistent with those in Example 1.

[0097] Example 6 The difference between this embodiment and Embodiment 1 is that the surface of the interface micro-anchoring transition layer is modified with active functional groups, including hydroxyl and carboxyl groups. That is, the prepared interface micro-anchoring transition layer is further post-processed, and the steps include: performing plasma etching on the interface micro-anchoring transition layer to introduce hydroxyl and carboxyl groups on the surface of the interface micro-anchoring transition layer.

[0098] The remaining preparation methods and parameters are consistent with those in Example 1.

[0099] Example 7 The difference between this embodiment and Embodiment 1 is that the dry electrode layer further includes a silane coupling agent KH-550, and the mass content of the silane coupling agent in the dry electrode layer is 0.25 wt%.

[0100] The remaining preparation methods and parameters are consistent with those in Example 1.

[0101] Example 8 The difference between this embodiment and Embodiment 1 is that the preparation process parameters of the nickel layer are adjusted so that the surface roughness Ra of the nickel layer is 15 nm.

[0102] The remaining preparation methods and parameters are consistent with those in Example 1.

[0103] Example 9 The difference between this embodiment and Embodiment 1 is that the preparation process parameters of the nickel layer are adjusted so that the surface roughness Ra of the nickel layer is 85 nm.

[0104] The remaining preparation methods and parameters are consistent with those in Example 1.

[0105] Example 10 The difference between this embodiment and Embodiment 1 is that the fabrication process parameters of the interface micro-anchoring transition layer are adjusted so that the thickness ratio of the nickel layer to the interface micro-anchoring transition layer is 2:1.

[0106] The remaining preparation methods and parameters are consistent with those in Example 1.

[0107] Example 11 The difference between this embodiment and Embodiment 1 is that the fabrication process parameters of the interface micro-anchoring transition layer are adjusted so that the thickness ratio of the nickel layer to the interface micro-anchoring transition layer is 6:1.

[0108] The remaining preparation methods and parameters are consistent with those in Example 1.

[0109] Comparative Example 1 This comparative example provides a pure copper foil with a thickness of 10 μm as a functional current collector.

[0110] The negative electrode provided in this comparative example includes the functional current collector as described above, and an electrode layer disposed on the surface of the functional current collector.

[0111] The electrode layer comprises a negative electrode active material, a binder, and a conductive agent. The binder is PVDF; the negative electrode active material is graphite; the mass content of the negative electrode active material in the electrode layer is 96 wt%; the mass content of the binder in the electrode layer is 2 wt%; the thickness of the electrode layer is 7 μm; and the conductive agent is conductive carbon black.

[0112] This embodiment also provides a method for preparing the above-mentioned negative electrode sheet, including the following steps: A negative electrode active material, binder, conductive agent and NMP solvent are mixed to obtain an electrode slurry; the electrode slurry is coated on the surface of the copper foil and dried to obtain the negative electrode sheet.

[0113] The remaining preparation methods and parameters are consistent with those in Example 1. Comparative Example 2 This comparative example provides a pure copper foil with a thickness of 10 μm as a functional current collector.

[0114] The negative electrode provided in this comparative example includes the functional current collector as described above, and a dry electrode layer disposed on the surface of the functional current collector.

[0115] The dry electrode layer comprises a negative electrode active material, a binder, and a conductive agent. The binder is PTFE; the negative electrode active material is graphite; the mass content of the negative electrode active material in the dry electrode layer is 96 wt%; the mass content of the binder in the dry electrode layer is 2 wt%; the thickness of the dry electrode layer is 7 μm; and the conductive agent is conductive carbon black.

[0116] The remaining preparation methods and parameters are consistent with those in Example 1.

[0117] Comparative Example 3 The only difference between this comparative example and the functional current collector in Example 1 is that the functional current collector does not have an interface micro-anchoring transition layer, that is, it does not have a nickel oxide layer.

[0118] The negative electrode provided in this comparative example includes the functional current collector as described above, and an electrode layer disposed on the surface of the functional current collector.

[0119] The electrode layer comprises a negative electrode active material, a binder, and a conductive agent. The binder is PVDF; the negative electrode active material is graphite; the mass content of the negative electrode active material in the electrode layer is 96 wt%; the mass content of the binder in the electrode layer is 2 wt%; the thickness of the electrode layer is 7 μm; and the conductive agent is conductive carbon black.

[0120] This embodiment also provides a method for preparing the above-mentioned negative electrode sheet, including the following steps: A negative electrode active material, binder, conductive agent and NMP solvent are mixed to obtain an electrode slurry; the electrode slurry is coated on the surface of the functional current collector and dried to obtain the negative electrode sheet.

[0121] Comparative Example 4 The difference between this comparative example and Example 1 is that the nickel layer is replaced with a copper layer.

[0122] The remaining preparation methods and parameters are consistent with those in Example 1.

[0123] Comparative Example 5 The difference between this comparative example and Example 1 is that the interface micro-anchoring transition layer is not provided.

[0124] The remaining preparation methods and parameters are consistent with those in Example 1.

[0125] Comparative Example 6 The difference between this comparative example and Example 1 is that in the dry electrode layer, PTFE is replaced with an equal mass of PVDF.

[0126] The remaining preparation methods and parameters are consistent with those in Example 1.

[0127] Performance testing The interface bonding performance of the dry negative electrode provided in the above embodiments and comparative examples was tested, namely the 180° peel strength test. The test steps included: cutting the electrode sheet into strips with a width of 20 mm, fixing the rigid substrate with double-sided tape, holding the free end of the electrode sheet with a tension clamp, and stretching at a speed of 50 mm / min. The test was completed at room temperature throughout the process, and the average peel force was recorded.

[0128] The lithium-ion batteries provided in the above embodiments and comparative examples were subjected to cycle performance tests and structural stability tests. The cycle performance test conditions included: 0.5C constant current charge-discharge, voltage range of 2.5-4.2V, and 500 cycles. The structural stability test conditions were: a constant temperature environment of 25℃ and an AC impedance test frequency range of 10 Hz. -2 ~10 6 At Hz, a 5mV AC disturbance voltage was applied, and the rate of change of interface resistance before and after 100 cycles was recorded.

[0129] The recyclability performance of the lithium-ion batteries provided in the above embodiments and comparative examples was tested. The test method included: ultrasonic treatment with deionized water for 30 minutes, and testing the residual rate of negative electrode active material on the surface of the functional current collector.

[0130] The test results are shown in Table 1.

[0131] Table 1 analyze: As shown in Table 1, this application replaces the traditional copper layer with a non-copper metal layer, fundamentally avoiding copper contamination while effectively improving the battery's mass energy density. The interface micro-anchoring transition layer with its uneven micro-anchoring structure can form a reliable mechanical interlock with the dry electrode layer, significantly enhancing the interfacial bonding force between the dry electrode and the functional current collector. Furthermore, the dual binder system in the dry electrode layer set on the surface of the interface micro-anchoring transition layer synergistically enhances the electrode cohesion and interfacial adhesion, forming a mechanical interlock with the non-metallic layer and the interface micro-anchoring transition layer, thus solving the problems of easy detachment and high impedance of the dry electrode. The overall structural design of this functional current collector can simultaneously solve the problems of heavy weight, serious recycling pollution, poor adhesion of the dry electrode, uneven lithium deposition, easy interface delamination, and insufficient stability under high loads associated with traditional copper foil, thereby significantly improving the battery's energy density, cycle stability, and lifespan. Furthermore, the dry anode constructed by combining the functional current collector with the dry electrode layer can achieve solvent-free green manufacturing, with controllable interfacial bonding force, and can achieve complete separation of the dry electrode layer and the functional current collector after use, greatly improving the recycling efficiency.

[0132] As can be seen from the comparison between Example 1 and Examples 8-9, if the surface roughness Ra of the nickel layer is too small, the surface of the nickel layer is too smooth, the mechanical interlocking effect with the interface micro-anchoring transition layer is weak, the peel strength decreases, and the interface impedance increase during cycling is significantly increased; if the surface roughness Ra of the nickel layer is too large, the sharp peaks on the surface of the nickel layer are prone to causing local current concentration, inducing lithium dendrite growth, accelerating battery capacity decay, and significantly increasing the amount of residual active material during electrode recycling.

[0133] A comparison of Examples 1 and 10-11 shows that if the thickness ratio of the nickel layer to the interface micro-anchoring transition layer is too small, the transition layer thickness will be too large, the overall conductive path will be blocked, the interface internal resistance will increase, and the battery cycle stability will deteriorate. If the thickness ratio of the nickel layer to the interface micro-anchoring transition layer is too large, the transition layer thickness will be insufficient, the number of surface uneven micro-anchoring structures will be too small, and it will be unable to form sufficient mechanical anchoring with the dry electrode, the interface peel strength will be reduced, and the electrode delamination will easily occur under long cycles.

[0134] As can be seen from the comparison between Example 1 and Comparative Example 1, if the traditional copper foil + wet electrode preparation technology is adopted, the high weight of the copper foil will reduce the energy density of the battery. At the same time, the active material is difficult to peel off during electrode recycling, and the residual rate is extremely high. The battery cycle capacity retention rate is much lower than that of the solution in this application, and the interface impedance increases significantly.

[0135] As can be seen from the comparison between Example 1 and Comparative Example 2, if the traditional copper foil + single binder is used to prepare dry electrodes, the bonding strength between the electrode and the current collector interface will decrease significantly; during the cycle, the active material of the electrode is prone to fall off, the battery capacity decay rate will accelerate, the interface impedance will increase significantly, and it will be difficult to meet the requirements of long-cycle operation.

[0136] As can be seen from the comparison between Example 1 and Comparative Example 3, if the technical route of preparing the functional current collector and wet electrode in Comparative Example 3 is adopted, the lightweight advantage of the system is lost, the nickel layer does not have lithium affinity properties, it is difficult to balance the lithium ion flux, and it is easy to cause uneven lithium deposition; the difficulty of separating and recycling the electrode and the current collector increases, and the overall cycle performance of the battery is significantly degraded.

[0137] As can be seen from the comparison between Example 1 and Comparative Example 4, if the nickel layer is replaced with a copper layer, the system will lose its lightweight advantage. At the same time, the copper layer lacks lithium-affinity properties, making it difficult to effectively control the lithium-ion flux balance and easily inducing uneven lithium deposition. In addition, this replacement will increase the difficulty of separating and recycling the electrode and the current collector, and the overall cycle performance of the battery will be significantly reduced.

[0138] As can be seen from the comparison between Example 1 and Comparative Example 5, if the interface micro-anchoring transition layer is not set, the system lacks the concave-convex micro-anchoring interlocking structure. The dry electrode and the metal substrate are only bonded by weak intermolecular interactions, and the interface peel strength is significantly reduced. During charge-discharge cycles, the interface is prone to delamination failure, the battery capacity decay is aggravated, and the interface impedance is greatly increased.

[0139] As can be seen from the comparison between Example 1 and Comparative Example 6, if PTFE is replaced with an equal mass of PVDF in the dry electrode layer, the electrode adhesion is insufficient, the interfacial peel strength decreases, the cycle capacity retention rate decreases, and the increase in interfacial impedance during the cycle process is significantly increased.

[0140] It should be noted that this application illustrates the process method through the above embodiments, but this application is not limited to the above process steps, that is, it does not mean that this application must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to this application, equivalent substitutions of the raw materials used in this application, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of this application.

Claims

1. A functional current collector for dry negative electrodes, characterized in that, The functional current collector includes: Polymer-based film; A non-copper metal layer is disposed on at least one side surface of the polymer base film; An interface micro-anchoring transition layer, having a concave-convex micro-anchoring structure, is disposed on the surface of the non-copper metal layer away from the polymer base film.

2. The functional current collector for dry negative electrode according to claim 1, characterized in that, The thickness of the polymer-based film is 10-20 μm; And / or, the thickness of the non-copper metal layer is 0.3-1 μm; And / or, the surface roughness Ra of the non-copper metal layer is 20-80 nm; And / or, the thickness ratio of the non-copper metal layer to the interface micro-anchoring transition layer is (3-5):

1.

3. The functional current collector for dry negative electrode according to claim 2, characterized in that, The thickness of the non-copper metal layer is 0.3-0.8 μm. And / or, the surface roughness Ra of the non-copper metal layer is 30-50 nm; And / or, the thickness ratio of the non-copper metal layer to the interface micro-anchoring transition layer is (3.5-4.5):

1.

4. The functional current collector for dry-process negative electrode according to any one of claims 1-3, characterized in that, The material of the non-copper metal layer includes any one or a combination of at least two of elemental cobalt, elemental nickel, nickel-cobalt alloy, nickel-titanium alloy, elemental titanium, or elemental chromium. And / or, the interface micro-anchoring transition layer includes a conductive carbon layer and / or a non-copper metal oxide layer.

5. The functional current collector for dry-process negative electrode according to any one of claims 1-4, characterized in that, The sheet resistance of the non-copper metal layer is ≤0.1Ω / sq; And / or, the interfacial peel strength of the non-copper metal layer is ≥1.2 N / cm; And / or, the feature size of the concave-convex micro-anchoring structure in the direction perpendicular to the surface of the non-copper metal layer is 10-500 nm; And / or, the concave-convex micro-anchoring structure includes an island-like structure and a particle-stacking structure; And / or, the surface of the interface micro-anchoring transition layer is modified with active functional groups, including hydroxyl and / or carboxyl groups.

6. A method for preparing a functional current collector for a dry negative electrode as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: Provide polymer-based films; A non-copper metal layer and an interface micro-anchoring transition layer are sequentially prepared on at least one side surface of the polymer base film to obtain the functional current collector for the dry negative electrode.

7. The preparation method according to claim 6, characterized in that, The preparation method of the non-copper metal layer includes electron beam evaporation or magnetron sputtering. And / or, the method for preparing the interface micro-anchoring transition layer includes chemical vapor deposition or physical vapor deposition; And / or, the prepared interfacial micro-anchoring transition layer is further post-processed, including the following steps: The interface micro-anchoring transition layer is etched to introduce active functional groups on the surface of the interface micro-anchoring transition layer, the active functional groups including hydroxyl and / or carboxyl groups.

8. A dry-process negative electrode, characterized in that, The dry negative electrode includes the functional current collector as described in any one of claims 1-5, and a dry electrode layer disposed on the surface of the functional current collector. The dry electrode layer comprises a negative electrode active material and a composite binder, wherein the composite binder comprises polytetrafluoroethylene and polyvinylidene fluoride.

9. The dry-process negative electrode according to claim 8, characterized in that, In the dry electrode layer, the mass content of the composite binder is 2-3 wt%; And / or, the mass ratio of the polytetrafluoroethylene to polyvinylidene fluoride is (0.8-1.2):1; And / or, the thickness of the dry electrode layer is 5-10 μm; And / or, the dry electrode layer further includes a silane coupling agent, wherein the silane coupling agent has a mass content of 0.1-0.5 wt% in the dry electrode layer.

10. A lithium-ion battery, characterized in that, The lithium-ion battery includes a dry negative electrode as described in claim 8 or 9.